1 PERTUMBUHAN EKONOMI DAN KETIMPANGAN ANTAR KABUPATEN / KOTA DI PROPINSI SUMATERA BARAT TAHUN 200 -2010 - , ALFONSO RAHMAT RIZA; , Dr. Luthfi Muta'ali, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The issue of income Regional development activities needs to balance between economic growth and equity. The refional development in West Sumatra visibly indicate there is inequality region. disparity that occurred in West Sumatra, are still clearly visible despite economic growth in the period 2001 - 2010 close to the average growth of the national economy. Economic growth accompanied by relatively high levels of disparity requires a scientific research to determine the relationship between the two variables. This study aims to analyze the growth and the expansion economic disparity derived from the value of GDP, the pattern of economic growth and disparity relations and provide policy recommendations. This research was conducted with analysis of secondary data by using quantitative analysis methods. Region disparity measured using analytical techniques Theil Index, Klassen typology to classify regions into four types of areas to find a picture of the pattern and structure of economic growth of a region. To look at the relationship between economic growth and disparity region using Pearson correlation. And Typology of relationship patterns of growth and disparity as the direction in policy and regional development. that o Research results show n the Typology Klassen, most of the areas in the districts of West Sumatra are the type Small, Grow, whereas most of the urban areas in the Great type, Stagnant. While the pace of economic growth in the West Sumatra district reaches 5.51% and 4.92% of the city area. Disparity figures higher for urban areas than in the district. And there is a negative relationship between economic growth and disparity region, which means if there is an increase in economic growth in the region, the level of disparity will decrease, and vice versa if the region's economic growth declined, the existing level of disparity increases. Priority areas are the Mentawai Islands regency, Sawahlunto and Pariaman